An overview of current mental health in the general population of Australia during the COVID-19 pandemic: Results from the COLLATE project - Rossell, Susan L (Psychiatry Res, 2021)
The novel coronavirus disease (COVID-19) poses mental health challenges globally; however, to date, there is limited community level data. This study reports on the COLLATE project (COvid-19 and you: mentaL heaLth in AusTralia now survEy), an ongoing study aimed at understanding the impact of the COVID-19 pandemic on Australian mental health and well-being. We addressed prevailing primary concerns related to the COVID-19 pandemic, current levels of negative emotions and risk factors predicting negative emotions. On April 1st to 4th 2020, 5158 adults from the general public completed an online survey. Participants ranked their top ten current primary concerns about COVID-19, and completed standardized measures of negative emotions. The top three primary concerns were related to health and well-being of family and loved ones. Levels of negative emotion were high. Modelling of predictors of negative emotions established several risk factors related to demographic variables, personal vulnerabilities, financial stresses, and social distancing perceptions; particularly being young, female, or having a mental illness diagnosis. The data provides important characterization of the current Australian mental health. It appears that specific groups may need special attention to ensure their mental health is protected. These results may provide direction for international researchers characterizing similar issues.